Pembuatan Job Sheet Kendali Motor Servo Menggunakan Variable Speed Drive - Randaka Saputra; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
One of the practicum courses for the D4 Industrial Electrical Engineering study program at the Electrical Engineering Department is the Electrical Machine Control Practicum. One of the materials given in the Electrical Machine Control Practicum is servo motor control. Along with technological developments, in the electrical energy conversion laboratory as a place for the Electrical Machine Control Practicum, VSD SIEMENS SINAMICS V90 training is available using the SINAMICS V-ASISTANT software which runs on the Windows operating system and communicates with the V90 drive via USB. Based on the observations made, the VSD SIEMENS SINAMICS V90 training does not yet have a manual or jobsheet as a guide for students and lecturers in carrying out practical activities. Therefore, in this study it is proposed to make a servo motor control jobsheet with vsd for practical electrical machine control using the SINAMICS V-ASISTANT software. The feasibility of the jobsheet is assessed from the validity, practicality and effectiveness tests with research procedures following the 4D development research method, which consists of the stages of defining, designing, developing and deploying stages. Based on the results of the tests carried out, the results of the validity test were obtained in the very valid category, the results of the practicality test in the very practical category and the results of the effectiveness test in the very effective category. So that the jobsheet can be considered feasible to be used as a guide in the practical implementation of electric machine control with VSD.